Prevalence and Predictive Factors of Female Sexual Dysfunction in a Sample of Saudi Women. Issue 1 (7th November 2020) - Madbouly, Khaled; Al-Anazi, Mohammed; Al-Anazi, Hanan; Aljarbou, Abdullah; Almannie, Raed; Habous, Mohamad; Binsaleh, Saleh
Abstract: Introduction: Female sexual dysfunction (FSD) is a common health problem that is inadequately investigated in Saudi Arabia. Aim: To assess the prevalence and predictors of FSD in a sample of Saudi women attending the primary care and gynecology clinics. Methods: A cross-sectional clinic-based survey involved Saudi women attending primary care and gynecology clinics in a teaching hospital in Riyadh during the period from January to June 2019. Data were collected using a structured interview questionnaire. Female sexual function has been evaluated by the Arabic version of the Female Sexual Function Index. Main outcome measures: The main outcome measure of this study was female sexual function using the Arabic version of the Female Sexual Function Index. Results: 200 Saudi women were included in this study. Their age ranged from 18 to 50 years. Most of the participants (88.5%) were fairly satisfied or satisfied with their spouse's sexual ability and 120 (60%) had a risk of FSD. Participants with FSD reported the lowest scores for arousal and desire domains (3.03 ± 1.3 and 3.12 ± 1.1, respectively) followed by orgasm domain (3.48 ± 1.4). Predictive factors for risk of FSD in our participants were age greater than 40 years ( P = .012), unemployment ( P = .035), low/moderate family income ( P = .014), dissatisfaction with the spouse's sexual ability ( P = .005), and higher weight ( P = .010) and height ( P = .043). Only age greater than 40 years ( P = .041), low family income ( P = .007), and dissatisfaction with spouse's sexual ability ( P = .011) sustained independent significance in a multivariate logistic regression analysis. Conclusion: A high prevalence of FSD was encountered in our sample of Saudi women. Desire and arousal were the most significantly affected domains followed by orgasmic problems. Age greater than 40 years, low socioeconomic level, and dissatisfaction with the spouse's sexual ability are the most significant predictors.